ENGLISH SKILL IMPROVEMENT AT GRADE 11 OF HOSPYTALITY MAJOR AT SMK TUNAS MUDA BERKARYA BATAM - Fasaaro Hulu; Tisrin Maulina Dewi; Fitria Meilina (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This activity is carried out to improve knowledge and skills in English for grade 11 SMK Tunas Muda Berkarya Batam, the department of Hospitality. Students were given material about speaking development, vocabulary field, correct pronunciation and tenses usage. The activity was carried out for four meetings. The methods of developing the skills of participants that were applied consisted of methods of discussion, presentation, conversation, group in pairs, describing pictures and practicing roles as a staff and a guest. The result of this training is the participant's ability can be measured from the observations of 65% and the results after the training increased to 90% there were improments in participants' knowledge and skills in speaking, vocabulary, pronunciation and use of grammar.